Natuurrampe en die voorsienigheid van God, met besondere verwysing na die beskouing van Johannes Calvyn - Potgieter, P. C. (Verbum et ecclesia, 2006)
It stands to reason that many of those believing in the providence of God will look for theological guidance when natural disasters of a catastrophic magnitude strike. This paper explores the reasoning of well-known theologians, and particularly John Calvin, in this regard endeavouring to develop a relevant contribution towards deeper insight in the extremely difficult issue of a theodicy. Contrary to a popular idea that Calvin adopted an extremely harsh line on providence by which God becomes responsible for every kind of disaster, it is argued that he maintains a fine balance between the loving grace of our heavenly Father and his righteous judgment over mankind who undermined his intended order of nature by sin. Argued from a Christological perspective, the faithful should respect both God's revelation and his hidden plan, which they will not be able to fathom in this life. Whatever happens, they should be pastorally guided to humble patience and perseverance in sincere hope on God’ s unquestionable faithfulness, and the firm belief that he will guide his creation to its true destination.